The Problem of Designing the User Interface in the Interactive Websites (website of the Faculty of Fine Arts and Ways of Developing it) (Al-Academy, 2018)
The interactive websites are the interaction between the product and the user, and interactive design is based on the user interface for communication and how the interface responds to the user and how to help him to achieve his goals and enjoy the use of the interface. The interactive design is based on the design of interactive programs, i.e., programs that directly interact with the user, taking into account the different culture of the audience, the age group and many other factors. An example for the use of the user interface: Web designs, smartphone application designs and it even includes computer operating systems and electronic game interface. The interaction is the communication between the source and the receiver. The websites contain many types of interaction that vary from website to another by type, such as social networking websites that allow the user to interact with other users. The website has become a means of interaction between users and not limited to the content of the website. Some websites allow the user to add text, images, and all multimedia and in turn allow other users to interact with the user's content and to see reactions and discussions about that content. Here is the problem of the current research represented by the following question: Is the design of the user interface is a shortcut and simplification for the user during the use? The importance of research is the benefit of the workers in the field of interactive design represented by the visual communication. The objective of the research is as follows:Identifying the user interface and its ability to meet the needs of the user and submitting a design proposal. The limits of the current research include: Websites of the Faculty of Fine Arts, University of Baghdad, Ministry of Higher Education of Iraq (2016-2017). Then, specific terms were defined for the subject matter (user interface, interactive designs).Concerning the theoretical framework and the previous studies, the theoretical framework consisted of two sections: the user interface and the interactive design. The most important indicators that emerged from the theoretical framework have been annexed. It includes two previous studies.As for the research procedures, the researcher adopted the descriptive approach (the method of content analysis) in the analysis of the research sample which is suitable to the research objectives. The research sample was chosen intentionally. The researcher came up with a number of results: Building websites depends on the main elements in the design and it applies to the websites in general, but their use can be changed according to the type of website, and although the website included elements yet they have not been fully, effectively and usefully exploited by the user. The research came up with a set of conclusions such as: the websites that give the user the freedom to interact, use, share opinions and engage in discussions are the ones that serve the user and give him the freedom to express. The researcher came up with a set of recommendations, including: paying attention to the principles and foundations of design in general and the structural principles in the design of interactive websites in particular.